1996
DOI: 10.1111/j.1939-1676.1996.tb02029.x
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Cavernous Sinus Syndrome in 4 Dogs and 8 Cats

Abstract: Cavernous sinus syndrome (CSS) is characterized by deficits in more than one of the cranial nerves (CN) that traverse the cavernous sinus at the base of the cranial vault: CN 111 (oculomotor), IV (trochlear), VI (abducens), and the first two branches of CN V (trigeminal). Records from 4 dogs and 8 cats with CSS diagnosed over a 14-year period were reviewed. The most common clinical signs were ophthalmoparesis or ophthalmoplegia, mydriasis with no direct or consensual pupillary light reflexes, ptosis, decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 8 publications
3
50
2
Order By: Relevance
“…Oculomotor lesions have been previously reported in the dog, but not alone 3 –7 . Oculomotor nerve injury has been reported in several cases of cavernous sinus syndrome in which CN IV, VI, and the ophthalmic and maxillary branches of CN V have also been involved 3 , 4 –7 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Oculomotor lesions have been previously reported in the dog, but not alone 3 –7 . Oculomotor nerve injury has been reported in several cases of cavernous sinus syndrome in which CN IV, VI, and the ophthalmic and maxillary branches of CN V have also been involved 3 , 4 –7 …”
Section: Discussionmentioning
confidence: 97%
“…There was no evidence of contralateral hemiparesis to suggest fascicular involvement in the substance of the mesencephalon 2 . At the other end of the pathway, there was no evidence of involvement of the cavernous sinus region as the trochlear (IV), abducens (VI), and trigeminal (V) functions appeared intact 3 –7 . This suggested that the lesion of the oculomotor nerve was located in the subarachnoid portion of the third nerve between its exit from the mesencephalic junction and its entrance into the cavernous sinus region.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…The middle cranial fossa syndrome is a well‐recognized syndrome in dogs characterized by variable impairment of these nerves . In the veterinary literature, this syndrome is usually referred to as cavernous sinus syndrome . However, this term should ideally be discarded, because these cranial nerves are not directly related to the cavernous sinus .…”
Section: Discussionmentioning
confidence: 99%
“…Ophthalmoplegia is the dominant symptom of a series of causes that may impair the parasympathetic pathway of the eye, with possible severe etiologies, such as cavernous sinus syndrome, trauma, hemorrhage or tumor 1,13 . Because of the peculiar anatomy of cranial nerve III nerve in the dog, parasympathetic denervation is possible, without affecting the other functions of cranial nerve III 7,12 .…”
Section: Discussionmentioning
confidence: 99%